Loss of Satb2 in the Cortex and Hippocampus Leads to Abnormal Behaviors in Mice - Zhang, Qiong; Huang, Ying; Zhang, Lei; Ding, Yu-Qiang; Song, Ning-Ning (Frontiers in Molecular Neuroscience, 2019)
Satb2-associated syndrome (SAS) is a genetic disorder that results from the deletion or mutation of one allele within the Satb2 locus. Patients with SAS show behavioral abnormalities, including developmental delay/intellectual disability, hyperactivity, and symptoms of autism. To address the role of Satb2 in SAS-related behaviors and generate an SAS mouse model, Satb2 was deleted in the cortex and hippocampus of Emx1-Cre; Satb2flox/flox (Satb2 conditional knockout [CKO]) mice. Satb2 CKO mice showed hyperactivity, increased impulsivity, abnormal social novelty, and impaired spatial learning and memory. Furthermore, we also found that the development of neurons in cortical layer IV was defective in Satb2 CKO mice, as shown by the loss of layer-specific gene expression and abnormal thalamocortical projections. In summary, the abnormal behaviors revealed in Satb2 CKO mice may reflect the SAS symptoms associated with Satb2 mutation in human patients, possibly due to defective development of cortical neurons in multiple layers including alterations of their inputs/outputs.